Accelerated carbonation of steel slag monoliths at low CO2 pressure – microstructure and strength development. Issue 36 (February 2020) - Nielsen, P.; Boone, M.A.; Horckmans, L.; Snellings, R.; Quaghebeur, M.
Highlights: accelerated carbonation of stainless steel slag can produce valuable construction materials. the compressive strength of the carbonated stainless steel compacts can be correlated with the CO2 uptake of the compacts. the correlation between CO2 uptake and compressive strength of the carbonated compacts is temperature dependent. the temperature dependence is linked to the resulting microstructure of the carbonated stainless steel slags. Abstract: Several studies have focused on the parameters that influence the CO2 -uptake of steel slags during mineral carbonation, however, less is known about the parameters that affect the strength development of the carbonated products. In this study monoliths with a compressive strength of 30–50 MPa were made by mineral carbonation of compacted stainless steel slag in an autoclave under mild operating conditions (i.e. 10–60 °C, 1.5 bar P total, and 5–100 % CO2 ). The influence of moisture content, CO2 concentration, temperature and exposure time on CO2 uptake and strength development were evaluated. In general a good correlation was observed between CO2 uptake and compressive strength of the monoliths. At different temperatures however the compressive strength as a function of CO2 uptake differed. The highest CO2 uptake was realized for carbonation at 60°, the resulting compressive strength however is lower than for experiments carried out at lower temperature. The microstructure indicated a difference in carbonate precipitation between the samples carbonated at different temperatures. In the samples carbonated at 10 and 20 °C the carbonate crystals mainly precipitated on the slag particle surfaces and at particle contacts, strengthening the particle packing of the compacts. At 60 °C carbonate crystals did initially not precipitate on particle surfaces, but most likely at the fluid-gas interfaces, which resulted in a different microstructure and lower compressive strengths for an equivalent CO2 uptake.